Wear-resistant and corrosion-resistant PVC (polyvinyl chloride) plastic and preparation process thereof
By adding isopropyl tris(dioctylpyrophosphateyloxy)titanate, hexagonal boron nitride and liquid nitrile rubber to PVC plastic, a layered stacking structure is formed, and perfluorooctane and phenyladium dichloride are used to form a Din-octyl formate solves the problem of insufficient wear resistance and corrosion resistance of PVC plastics, and achieves excellent wear resistance and corrosion resistance.
Patent Information
- Application Number
- CN202411661500.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-20
- Publication Date
- 2025-01-14
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The wear-resistant and corrosion-resistant properties of existing PVC plastics are weak, resulting in short service life, many repairs and high replacement costs, and are susceptible to harmful substances caused by acid and alkali corrosion, which can cause harm to physical health.
By adding isopropyl tris(dioctylpyrophosphateyloxy)titanate and hexagonal boron nitride to the polyvinyl chloride resin matrix, the interface binding force is increased, and the hexagonal boron nitrile rubber is coated with liquid nitrile rubber. It is uniformly dispersed to form a layer-stacked barrier structure; at the same time, the addition of perfluorooctane reduces surface resistance and improves flexibility, and the addition of din-octyl phthalate reduces the friction coefficient, and optimizes the wear resistance of the finished product.
It significantly improves the corrosion resistance and wear resistance of PVC plastics, extends service life, reduces wear and repair costs, and reduces the migration of harmful substances caused by acid and alkali corrosion, and improves the safety and reliability of the materials.
Smart Images

Figure BDA0005143492420000021 
Figure BDA0005143492420000041 
Figure BDA0005143492420000051
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of plastic preparation, and in particular relates to wear-resistant and corrosion-resistant PVC plastic and a preparation process thereof. Background Art
[0002] Polyvinyl chloride is one of the most widely used general-purpose plastics in the world. It is widely used in the fields of footwear, building materials, wires, industrial products, daily necessities, floor coverings, artificial leather, pipes, packaging films and sealing materials. In these fields, wear-resistant and corrosion-resistant materials are often needed to manufacture various utensils to ensure the safety and reliability of the production process. If the material is not resistant to acid and alkali corrosion, it is easy to cause a large amount of waste of raw materials and the life safety of construction workers. At the same time, the migration of harmful substances caused by alkali corrosion will again cause harm to people's health; and if the material is not wear-resistant, it is easy to cause a short service life of the material, more maintenance times and high replacement costs. Although there are many PVC products on the market, their wear resistance and corrosion resistance are still lacking. Therefore, it is particularly necessary to provide a PVC product with good wear resistance and corrosion resistance. Summary of the invention
[0003] The purpose of the present invention is to provide a wear-resistant and corrosion-resistant PVC plastic and its preparation process. The polyvinyl chloride resin matrix and hexagonal boron nitride are connected by adding isopropyl tri (dioctyl pyrophosphate acyloxy) titanate in the raw materials to increase the interface bonding force between the two; at the same time, the hexagonal boron nitride is coated with liquid nitrile rubber to achieve uniform dispersion of the hexagonal boron nitride in the polyvinyl chloride resin matrix; based on the premise of good dispersibility and bonding, the lamellar hexagonal boron nitride plays the characteristics of its own lamellar structure very well, and is evenly dispersed in the polyvinyl chloride resin matrix to form a layered barrier structure, thereby achieving the purpose of corrosion resistance. At the same time, the present invention also reduces the surface resistance and improves the flexibility of the finished product by adding perfluorooctane; adds di-n-octyl phthalate to reduce the surface friction coefficient of the finished product and reduce wear, thereby making the finished product have excellent wear resistance; solves the problem of weak wear resistance and corrosion resistance of PVC plastic in the prior art.
[0004] The purpose of the present invention can be achieved through the following technical solutions:
[0005] A wear-resistant and corrosion-resistant PVC plastic, comprising the following raw materials in parts by weight:
[0006]
[0007] As a preferred embodiment of the present invention, the wear-resistant and corrosion-resistant PVC plastic further comprises 15-20 parts by weight of sodium hydroxide solution and 3-5 parts by weight of isopropanol.
[0008] As a preferred embodiment of the present invention, the mass fraction of the sodium hydroxide solution is 20-25%.
[0009] As a preferred embodiment of the present invention, the preparation process of the wear-resistant and corrosion-resistant PVC plastic comprises the following steps:
[0010] S10, pre-treating part of the raw materials to obtain pre-treated hexagonal boron nitride and a mixture for standby use;
[0011] S20, preparing intermediate material;
[0012] S30, preparing wear-resistant and corrosion-resistant PVC plastic finished products.
[0013] As a preferred solution of the present invention, step S10 specifically includes the following steps:
[0014] S11, mixing the sodium hydroxide solution and the hexagonal boron nitride evenly and performing ultrasonic reaction, then controlling the temperature and stirring the reaction, controlling the speed of centrifugation after the reaction is completed, washing and drying after the centrifugation to obtain pretreated hexagonal boron nitride for standby use;
[0015] S12, stirring the polyvinyl chloride resin and 1,2-diisononyl phthalate uniformly at a controlled speed to obtain a mixture for later use.
[0016] As a preferred embodiment of the present invention, the ultrasonic reaction time in step S11 is 60-70 min; the temperature of the temperature-controlled stirring reaction is 95-100°C, and the reaction time is 12-14 h; the speed of the speed-controlled centrifugation is 7500-7800 r / min, and the time is 10-12 min; and the number of washing times is 3-5 times.
[0017] As a preferred embodiment of the present invention, the speed of the controlled stirring in step S12 is 340-390 rpm.
[0018] As a preferred embodiment of the present invention, step S20 specifically includes the following steps: mixing isopropyl tri(dioctyl pyrophosphate) titanate and isopropanol, adding pretreated hexagonal boron nitride, mixing evenly and reacting ultrasonically, then controlling the temperature and stirring the reaction, controlling the speed of centrifugation after the reaction is completed, washing and drying after the centrifugation is completed to obtain an intermediate material.
[0019] As a preferred embodiment of the present invention, the mixing and stirring time is 3-5 minutes; the ultrasonic reaction time is 10-12 minutes; the temperature of the temperature-controlled stirring reaction is 70-75°C, and the time is 0.5-1h; the speed-controlled centrifugation is 2-3 times at a speed of 6000-7000r / min, each time for 3-5 minutes; the number of washing times is 3-5 times.
[0020] As a preferred embodiment of the present invention, step S30 specifically includes the following steps: mixing the liquid nitrile rubber and the intermediate material at a controlled speed, then adding the mixed material, di-n-octyl phthalate, perfluorooctane, polyethylene wax and zinc stearate to mix evenly, then stirring at a controlled temperature and speed, adjusting the extruder temperature setting after stirring, and extruding and granulating to obtain a wear-resistant and corrosion-resistant PVC plastic product.
[0021] As a preferred embodiment of the present invention, the speed of the speed-controlled mixing is 22000-23000r / min, and the time is 2-2.5min; the temperature of the temperature-controlled and speed-controlled stirring is 160-170°C, the speed is 1000-1100rmp, and the time is 10-15min; the temperature of the extruder is set to: 130-140°C for zone one, 135-150°C for zone two, 140-160°C for zone three, 160-173°C for zone four, and 140-155°C for zone five.
[0022] Beneficial effects of the present invention:
[0023] (1) The present invention adds hexagonal boron nitride, isopropyl tri(dioctyl pyrophosphate) titanate and liquid nitrile rubber, so that the obtained PVC finished product has excellent corrosion resistance. This is because the present invention grafts isopropyl tri(dioctyl pyrophosphate) titanate on the surface of hexagonal boron nitride to play a bridge role connecting the polyvinyl chloride resin matrix and the hexagonal boron nitride, thereby increasing the interfacial bonding force between the two; at the same time, the hexagonal boron nitride is coated with liquid nitrile rubber, and the liquid nitrile rubber has good compatibility with the polyvinyl chloride resin matrix, thereby achieving uniform dispersion of the hexagonal boron nitride in the polyvinyl chloride resin matrix; based on the premise of good dispersibility and bonding, the lamellar hexagonal boron nitride has excellently exerted the characteristics of its own lamellar structure, and is evenly dispersed in the polyvinyl chloride resin matrix to form a stacked barrier structure, extending the path of corrosion penetration and increasing the difficulty of penetration, thereby achieving the purpose of corrosion resistance.
[0024] (2) The present invention adds perfluorooctane, and grafts perfluorooctane with lower surface energy and better lubricity on the surface of the polyvinyl chloride resin molecular chain to reduce the surface resistance of the finished product and improve the flexibility; at the same time, di-n-octyl phthalate interacts with the polyvinyl chloride resin molecular chain to reduce the surface friction coefficient of the finished product and reduce abrasion; thereby optimizing the wear resistance and scratch resistance of the finished product, so that the finished product has excellent wear resistance. DETAILED DESCRIPTION
[0025] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0026] Example 1
[0027] A wear-resistant and corrosion-resistant PVC plastic, comprising the following raw materials in parts by weight:
[0028]
[0029]
[0030] The preparation process of the wear-resistant and corrosion-resistant PVC plastic comprises the following steps:
[0031] S10, pre-treating part of the raw materials to obtain pre-treated hexagonal boron nitride and a mixture for standby use:
[0032] S11, mixing the sodium hydroxide solution and hexagonal boron nitride evenly and ultrasonically reacting for 65 minutes, then controlling the temperature at 95°C and stirring for 14 hours, centrifuging at 7500r / min for 12 minutes after the reaction is completed, washing 5 times and drying after the centrifugation to obtain pretreated hexagonal boron nitride for standby use;
[0033] S12, stirring the polyvinyl chloride resin and diisononyl 1,2-phthalate at a controlled speed of 365 rpm to obtain a mixture for later use;
[0034] S20, preparing an intermediate material: mixing isopropyl tri(dioctyl pyrophosphate acyloxy) titanate and isopropanol for 4 minutes, adding pretreated hexagonal boron nitride, mixing evenly and reacting by ultrasonication for 10 minutes, then controlling the temperature at 75°C and stirring for 0.5 hours, centrifuging at 7000 r / min for 2 times, each time for 4 minutes, washing 3 times and drying after the centrifugation to obtain an intermediate material;
[0035] S30, preparing wear-resistant and corrosion-resistant PVC plastic finished products: liquid nitrile rubber and intermediate material are mixed at a speed of 22000r / min for 2min, then the mixed material, di-n-octyl phthalate, perfluorooctane, polyethylene wax and zinc stearate are added and mixed evenly, and then the temperature is controlled at 165°C and the speed is controlled at 1050rmp to stir for 15min. After the stirring is completed, the temperature of the extruder is adjusted to: 130°C for zone 1, 150°C for zone 2, 150°C for zone 3, 160°C for zone 4 and 148°C for zone 5, and granulation is performed by extrusion to obtain wear-resistant and corrosion-resistant PVC plastic finished products.
[0036] Example 2
[0037] A wear-resistant and corrosion-resistant PVC plastic, comprising the following raw materials in parts by weight:
[0038]
[0039] The preparation process of the wear-resistant and corrosion-resistant PVC plastic comprises the following steps:
[0040] S10, pre-treating part of the raw materials to obtain pre-treated hexagonal boron nitride and a mixture for standby use:
[0041] S11, mixing the sodium hydroxide solution and hexagonal boron nitride evenly and ultrasonically reacting for 60 minutes, then controlling the temperature at 98°C and stirring for 12 hours, centrifuging at 7650r / min for 10 minutes after the reaction, washing 3 times after the centrifugation and drying to obtain pretreated hexagonal boron nitride for standby use;
[0042] S12, stirring the polyvinyl chloride resin and diisononyl 1,2-phthalate at a controlled speed of 390 rpm to obtain a mixture for later use;
[0043] S20, preparing an intermediate material: mixing isopropyl tri(dioctyl pyrophosphate acyloxy) titanate and isopropanol for 5 minutes, adding pretreated hexagonal boron nitride, mixing evenly and reacting by ultrasonication for 11 minutes, then controlling the temperature at 70°C and stirring for 0.5 hours, centrifuging at 6000 r / min for 3 times, each time for 5 minutes, washing 4 times and drying after the centrifugation to obtain an intermediate material;
[0044] S30, preparing wear-resistant and corrosion-resistant PVC plastic finished products: liquid nitrile rubber and intermediate material are mixed at a speed of 23000r / min for 2min, then the mixed material, di-n-octyl phthalate, perfluorooctane, polyethylene wax and zinc stearate are added and mixed evenly, and then the temperature is controlled at 170℃ and the speed is controlled at 1000rmp to stir for 10min. After the stirring is completed, the temperature of the extruder is adjusted to: 140℃ for zone 1, 135℃ for zone 2, 140℃ for zone 3, 173℃ for zone 4 and 155℃ for zone 5, and granulation is performed by extrusion to obtain wear-resistant and corrosion-resistant PVC plastic finished products.
[0045] Example 3
[0046] A wear-resistant and corrosion-resistant PVC plastic, comprising the following raw materials in parts by weight:
[0047]
[0048] The preparation process of the wear-resistant and corrosion-resistant PVC plastic comprises the following steps:
[0049] S10, pre-treating part of the raw materials to obtain pre-treated hexagonal boron nitride and a mixture for standby use:
[0050] S11, mixing the sodium hydroxide solution and hexagonal boron nitride evenly and ultrasonically reacting for 70 minutes, then controlling the temperature at 100° C. and stirring for 13 hours, and after the reaction is completed, centrifuging at a speed of 7800 r / min for 11 minutes, washing 4 times and drying after the centrifugation, to obtain pretreated hexagonal boron nitride for standby use;
[0051] S12, stirring the polyvinyl chloride resin and diisononyl phthalate at a controlled speed of 340 rpm to obtain a mixture for later use;
[0052] S20, preparing an intermediate material: mixing isopropyl tri(dioctyl pyrophosphate acyloxy) titanate and isopropanol and stirring for 3 minutes, adding pretreated hexagonal boron nitride and mixing evenly and ultrasonically reacting for 12 minutes, then controlling the temperature at 73°C and stirring to react for 1 hour, centrifuging at 6500 r / min for 3 times after the reaction, washing 5 times and drying after the centrifugation to obtain an intermediate material;
[0053] S30, preparing wear-resistant and corrosion-resistant PVC plastic finished products: liquid nitrile rubber and intermediate material are mixed at a speed of 22500r / min for 2.5min, then the mixed material, di-n-octyl phthalate, perfluorooctane, polyethylene wax and zinc stearate are added and mixed evenly, and then the temperature is controlled at 160℃ and the speed is controlled at 1100rmp to stir for 13min. After stirring, the temperature of the extruder is adjusted to: 135℃ for zone 1, 143℃ for zone 2, 160℃ for zone 3, 167℃ for zone 4 and 140℃ for zone 5, and granulation is performed to obtain wear-resistant and corrosion-resistant PVC plastic finished products.
[0054] Comparative Examples 1-3
[0055] Compared with Example 3, the difference is that the weight parts of hexagonal boron nitride, isopropyl tri(dioctyl pyrophosphate) titanate and liquid nitrile rubber in Comparative Examples 1-3 are as shown in Table 1, and the other parameters and operating steps remain unchanged.
[0056] Table 1
[0057]
[0058] Comparative Example 4
[0059] Compared with Example 3, the difference is that in Comparative Example 4, no perfluorooctane is added, and the other parameters and operating steps remain unchanged.
[0060] Comparative Example 5
[0061] Compared with Example 3, the difference is that in Comparative Example 5, no di-n-octyl phthalate is added, and the other parameters and operating steps remain unchanged.
[0062] Performance Testing
[0063] (1) Corrosion resistance, acid and alkali resistance: The finished products obtained in Examples 1-3 and Comparative Examples 1-3 were pressed into 3 mm thin slices, and then the thin slices were immersed in concentrated sulfuric acid with a pH of 2-3 and potassium hydroxide with a pH of 11-12 for 72 hours, respectively, to conduct corrosion resistance and acid and alkali resistance tests. The same staff observed the corrosion resistance of the products according to the following standards:
[0064] A. No corrosion (no discoloration or cracks on the surface and good gloss);
[0065] B. Almost no corrosion (there is a little discoloration or cracks on the surface and the gloss is slightly faded);
[0066] C. Erosion (obvious surface discoloration or many cracks and obvious fading of gloss);
[0067] The results are shown in Table 2.
[0068] (2) Wear test: The finished products obtained in Examples 1-3 and Comparative Examples 4-5 were respectively pressed into 3 mm thin slices and scraped 300 times on a wear tester under the same conditions. The change in wear before and after scraping was observed. The results are shown in Table 2.
[0069] Table 2
[0070] Corrosion resistance, acid and alkali resistance Wear amount / g Example 1 A 0.44 Example 2 A 0.45 Example 3 A 0.42 Comparative Example 1 B —— Comparative Example 2 B —— Comparative Example 3 B —— Comparative Example 4 —— 0.86 Comparative Example 5 —— 0.79
[0071] It can be seen from Table 2 that the PVC finished product prepared by the present invention has excellent corrosion resistance. In detail, it can be seen from the data of Examples 1-3 and Comparative Examples 1-3 that the present invention adds isopropyl tri(dioctyl pyrophosphate acyloxy) titanate to increase the interface bonding force between hexagonal boron nitride and the polyvinyl chloride resin matrix; at the same time, the hexagonal boron nitride is coated with liquid nitrile rubber to achieve uniform dispersion of the hexagonal boron nitride in the polyvinyl chloride resin matrix; based on the premise of good dispersibility and bonding, the lamellar hexagonal boron nitride has excellently exerted the characteristics of its own lamellar structure, and is evenly dispersed in the polyvinyl chloride resin matrix to form a stacked barrier structure, extending the path of corrosion penetration and increasing the difficulty of penetration, thereby achieving the purpose of corrosion resistance.
[0072] It can be seen from the data of Examples 1-3 and Comparative Examples 4-5 that the PVC finished product prepared by the present invention has excellent wear resistance, because, in the present invention, perfluorooctane is added, and perfluorooctane with lower surface energy and better lubricity is grafted on the surface of the polyvinyl chloride resin molecular chain to reduce the surface resistance of the finished product and improve the flexibility; at the same time, di-n-octyl phthalate interacts with the polyvinyl chloride resin molecular chain to reduce the surface friction coefficient of the finished product and reduce abrasion; thereby optimizing the wear resistance and scratch resistance of the finished product, so that the finished product has excellent wear resistance.
[0073] In the description of the specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.
[0074] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.
Claims
1. A wear-resistant and corrosion-resistant PVC plastic, characterized in that: The wear-resistant and corrosion-resistant PVC plastic comprises the following raw materials in parts by weight:
2. The wear-resistant and corrosion-resistant PVC plastic according to claim 1, characterized in that: The wear-resistant and corrosion-resistant PVC plastic also includes 15-20 parts by weight of sodium hydroxide solution and 3-5 parts by weight of isopropanol.
3. A process for preparing the wear-resistant and corrosion-resistant PVC plastic as claimed in claim 2, characterized in that: The preparation process of the wear-resistant and corrosion-resistant PVC plastic comprises the following steps: S10, pre-treating part of the raw materials to obtain pre-treated hexagonal boron nitride and a mixture for standby use; S20, preparing intermediate material; S30, preparing wear-resistant and corrosion-resistant PVC plastic finished products.
4. The preparation process of the wear-resistant and corrosion-resistant PVC plastic according to claim 3, characterized in that: The step S10 specifically includes the following steps: S11, mixing the sodium hydroxide solution and the hexagonal boron nitride evenly and performing ultrasonic reaction, then controlling the temperature and stirring the reaction, controlling the speed of centrifugation after the reaction is completed, washing and drying after the centrifugation to obtain pretreated hexagonal boron nitride for standby use; S12, stirring the polyvinyl chloride resin and 1,2-diisononyl phthalate uniformly at a controlled speed to obtain a mixture for later use.
5. The preparation process of the wear-resistant and corrosion-resistant PVC plastic according to claim 4, characterized in that: The ultrasonic reaction time of step S11 is 60-70 minutes; the temperature of the temperature-controlled stirring reaction is 95-100°C, and the reaction time is 12-14 hours; the speed of the speed-controlled centrifugation is 7500-7800 r / min, and the time is 10-12 minutes; the number of washing times is 3-5 times.
6. The process for preparing the wear-resistant and corrosion-resistant PVC plastic according to claim 4, characterized in that: The speed of the controlled stirring in step S12 is 340-390 rpm.
7. The preparation process of the wear-resistant and corrosion-resistant PVC plastic according to claim 3, characterized in that: The step S20 specifically includes the following steps: mixing isopropyl tri(dioctyl pyrophosphate) titanate and isopropanol, adding pretreated hexagonal boron nitride, mixing evenly and reacting with ultrasound, then controlling the temperature and stirring the reaction, controlling the speed of centrifugation after the reaction is completed, washing and drying after the centrifugation is completed to obtain an intermediate material.
8. The process for preparing the wear-resistant and corrosion-resistant PVC plastic according to claim 7, characterized in that: The mixing and stirring time is 3-5 minutes; the ultrasonic reaction time is 10-12 minutes; the temperature of the temperature-controlled stirring reaction is 70-75°C, and the time is 0.5-1h; the speed-controlled centrifugation is 2-3 times at a speed of 6000-7000r / min, each time for 3-5 minutes; the number of washing times is 3-5 times.
9. The process for preparing the wear-resistant and corrosion-resistant PVC plastic according to claim 3, characterized in that: The step S30 specifically includes the following steps: mixing the liquid nitrile rubber and the intermediate material at a controlled speed, then adding the mixed material, di-n-octyl phthalate, perfluorooctane, polyethylene wax and zinc stearate to mix evenly, then stirring at a controlled temperature and speed, adjusting the temperature setting of the extruder after the stirring is completed, and extruding and granulating to obtain a wear-resistant and corrosion-resistant PVC plastic product.
10. The process for preparing the wear-resistant and corrosion-resistant PVC plastic according to claim 9, characterized in that: The speed of the speed-controlled mixing is 22000-23000r / min, and the time is 2-2.5min; the temperature of the temperature-controlled and speed-controlled stirring is 160-170°C, the speed is 1000-1100rmp, and the time is 10-15min; the temperature of the extruder is set to: 130-140°C for zone one, 135-150°C for zone two, 140-160°C for zone three, 160-173°C for zone four, and 140-155°C for zone five.
Citation Information
Patent Citations
Alkali-corrosion-resistant high-strength flexible polyvinyl chloride membrane material and preparation method thereof
CN113214571A